A NEW COPPER (II)-IMIDAZOLE DERIVATIVE EFFECTIVELY INHIBITS REPLICATION OF DENV-2 IN VERO CELL - Sucipto, Teguh Hari; Churrotin, Siti; Setyawati, Harsasi; Martak, Fahimah; Mulyatno, Kris Cahyo; Amarullah, Ilham Harlan; Kotaki, Tomohiro; Kameoka, Masanori; Kameoka, Masanori; Yotopranoto, Subagyo; Soegijanto, Soegeng (African Journal of Infectious Diseases (AJID), 2018)
Background: Dengue is a kind of infectious disease that was distributed in the tropical and sub-tropical areas. To date, there is no clinically approved dengue vaccine or antiviral for humans, even though there have been great efforts towards this end. Therefore, finding the effective compound against dengue virus (DENV) replication is very important. Among the complex compounds, copper(II)-imidazole derivatives are of interest because of their biological and medicinal benefits. Materials and Methods: In the present study, antiviral activity of [Cu(2,4,5-triphenylimidazole)2]n, was evaluated against different stages of dengue virus type 2 (DENV-2) replication in Vero cell using focus forming unit reduction assay and quantitative ELISA. Results: [Cu(2,4,5-triphenylimidazole)2]n inhibited DENV-2 replication in Vero cells with IC50 = 2.3 μg/ml and SI= 19.42 when cells were treated 2 days after virus infection, whereas its CC50 for cytotoxicity to Vero cells was 44.174 μg/ml. Conclusion: The compound has high anti-DENV2 activity, less toxicity, and a high possibility to be considered a drug candidate.